Increased FOXM1 Expression by Cisplatin Inhibits Paclitaxel-Related Apoptosis in Cisplatin-Resistant Human Oral Squamous Cell Carcinoma (OSCC) Cell Lines - Choi, Hyeong Sim (Int J Mol Sci, 2020)
Cisplatin and paclitaxel are commonly used to treat oral cancer, but their use is often limited because of acquired drug resistance. Here, we tested the effects of combined cisplatin and paclitaxel on three parental (YD-8, YD-9, and YD-38) and three cisplatin-resistant (YD-8/CIS, YD-9/CIS, and YD-38/CIS) oral squamous cell carcinoma (OSCC) cell lines using cell proliferation assays and combination index analysis. We detected forkhead box protein M1 (FOXM1) mRNA and protein expression via real-time qPCR and Western blot assays. Cell death of the cisplatin-resistant cell lines in response to these drugs with or without a FOXM1 inhibitor (forkhead domain inhibitory compound 6) was then measured by propidium iodide staining and TdT dUTP nick end labeling (TUNEL) assays. In all six OSCC cell lines, cell growth was more inhibited by paclitaxel alone than combination therapy. Cisplatin-induced overexpression of FOXM1 showed the same trend only in cisplatin-resistant cell lines, indicating that it was associated with inhibition of paclitaxel-related apoptosis. In summary, these results suggest that, in three cisplatin-resistant cell lines, the combination of cisplatin and paclitaxel had an antagonistic effect, likely because cisplatin blocks paclitaxel-induced apoptosis. Cisplatin-induced FOXM1 overexpression may explain the failure of this combination.